2018
DOI: 10.1007/s11103-018-0795-9
|View full text |Cite
|
Sign up to set email alerts
|

Exon junction complex (EJC) core genes play multiple developmental roles in Physalis floridana

Abstract: Key messageMolecular and functional characterization of four gene families of the Physalis exon junction complex (EJC) core improved our understanding of the evolution and function of EJC core genes in plants.AbstractThe exon junction complex (EJC) plays significant roles in posttranscriptional regulation of genes in eukaryotes. However, its developmental roles in plants are poorly known. We characterized four EJC core genes from Physalis floridana that were named PFMAGO, PFY14, PFeIF4AIII and PFBTZ. They shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 92 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…However, this concern is allayed by two arguments. First, while initial reports suggested only a low silencing activity with tobacco-rattle virus (TRV)-mediated VIGS in pollen, recent experiments using TRV-VIGS have found strong effects on pollen development, either by affecting genes that appear to act directly in the pollen (33) or genes indirectly required for pollen development in the tapetal cells of the anthers (34,35). Second, the genetics of heterostyly in Primula suggests that the P gene acts in diploid sporophytic cells rather than in the haploid pollen, because S-morph flowers generate uniform pollen, both regarding its size and male incompatibility type, rather than the 1:1 segregation expected if the P gene acted in the haploid pollen itself.…”
Section: Resultsmentioning
confidence: 99%
“…However, this concern is allayed by two arguments. First, while initial reports suggested only a low silencing activity with tobacco-rattle virus (TRV)-mediated VIGS in pollen, recent experiments using TRV-VIGS have found strong effects on pollen development, either by affecting genes that appear to act directly in the pollen (33) or genes indirectly required for pollen development in the tapetal cells of the anthers (34,35). Second, the genetics of heterostyly in Primula suggests that the P gene acts in diploid sporophytic cells rather than in the haploid pollen, because S-morph flowers generate uniform pollen, both regarding its size and male incompatibility type, rather than the 1:1 segregation expected if the P gene acted in the haploid pollen itself.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, four core exon junction complex core genes in P. floridana —namely, PFMAGO , PFY14 , PFeIF4AIII , and PFBTZ —have been found to play diverse developmental roles in carpel functionality and environmental stress responses. Furthermore, an intron retention in the transcript of DYT1 was detected in the mutated flowers of P. floridana indicating its significance in floral development ( Gong et al., 2018 ). These works provide us with candidate genes for studying the growth and development of Physalis plants.…”
Section: Identification Of Functional Genesmentioning
confidence: 99%
“…Our results also indicated a mago nashi family protein to be a good candidate for SCN tolerance. Mago nashi protein is a key component of the exon junction complex (EJC) [38]. The involvement of mago nashi protein in plant defense pathways against pathogens remains poorly understood.…”
Section: Plos Onementioning
confidence: 99%
“…The involvement of mago nashi protein in plant defense pathways against pathogens remains poorly understood. However, Gong et al [38] reported that one of the genes found in the EJC complex is involved in plant growth and development. In this study, we reported loci affecting tolerance index based on biomass reduction under SCN infestation in soybean.…”
Section: Plos Onementioning
confidence: 99%